THE SOCIAL AND EDUCATIONAL CRITICISM OF GREEK CLASSICAL PHILOSOPHERS - Barbosa, Cloves; Wilson Tafner Junior, Armando (Revista Gênero e Interdisciplinaridade, 2025)
This paper introduce the them about relationship between classics greeks philosophy thing and social problems view. That problems are importante that it shows the divers position between philosophy and sofists during the higth greek people age. This problems presente the thems between philosophy and sofista about social, economic, and cultur problems during political and social changes into classics Greeks.